Menilai Kesetaraan dan Akurasi Qibla on Compass Aplikasi Miqat terhadap Metode Azimuth Geodesi: Analisis Galat Absolut, Bland-Altman, dan TOST - Andi Jusran Kasim; Rahman Subha; Fatri Sagita; Noercholis Rafid. A; Maryam U (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to evaluate the accuracy level of the Miqat Play Store application, tested in 36 mosques by comparing the results with the geodetic azimuth reference coordinates WGS84. The method used is quantitative observational, with measurements taken three times at each location using the Miqat application on various types of Android smartphones. The results of the analysis show a difference between the geodetic azimuth and Miqat with an absolute error between -0.7278° and 0.6523°, an average error of -0.19295° and a standard deviation of 0.1982°. Bland-Altman analysis showed that the difference between the two methods was within acceptable limits, with an upper limit (ULA) of 0.1956° and a lower limit (LLA) of -0.5815°. The TOST equivalence test showed an average difference of 0.193°, which was smaller than the tolerance of ±0.5°, so the two methods could be considered mathematically equivalent. This study concludes that Miqat is suitable for use as an aid in determining the azimuth of the compass qibla in controlled environmental conditions and with good magnetic sensor calibration.